Gallstone-Related Abdominal Abscess 8 Years After Laparoscopic Cholecystectomy - Dobradin, Andrew (Society of Laparoendoscopic Surgeons, 2013)
BACKGROUND: A common intraoperative complication during laparoscopic cholecystectomy is gallbladder perforation with spillage of gallstones. The undesirable consequence of spilled gallstones is the formation of abscesses months or years after an operation. CASE DESCRIPTION: Our clinical report describes an intraabdominal abscess formation in an 82-year-old man that developed 8 years after a laparoscopic cholecystectomy. A computed tomography scan of the abdomen showed an elongated fluid collection in the right abdominal compartment musculature at the level of the internal oblique muscle. Abdominal ultrasonography confirmed a large fluid collection, with 2 echogenic masses in the dependent portion. Incision and drainage of the abscess were performed, and 2 gallstones were found. CONCLUSION: Any unusual collection of fluid in the perihepatic space and abdominal wall in the area of the surgical incision in a patient with a remote history of cholecystectomy should be evaluated for abscess related to retained gallstone. Early abscess formation is usually diagnosed and treated by the surgeon. However, the late manifestation might be a clinical problem seen in the primary care physician's office. Therefore, the primary care physician should incorporate diagnosis of gallstone-related abscess in patients with abdominal abscess formation of unknown etiology.